2017
DOI: 10.21307/jofnem-2017-051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cover Crops on Pratylenchus penetrans and the Nematode Community in Carrot Production

Abstract: Cover cropping is a common practice in U.S. Midwest carrot production for soil conservation, and may affect soil ecology and plant-parasitic nematodes-to which carrots are very susceptible. This study assessed the impact of cover crops-oats (Avena sativa), radish (Raphanus sativus) cv. Defender, rape (Brassica napus) cv. Dwarf Essex, and a mixture of oats and radish-on plantparasitic nematodes and soil ecology based on the nematode community in Michigan carrot production systems. Research was conducted at two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 48 publications
(70 reference statements)
1
9
1
Order By: Relevance
“…It is known that black fallow in general has a negative effect on the population of P. penetrans (Pudasaini et al, 2006;Viaene et al, 2006). However, it was reported that at low population densities the number of nematodes can remain the same (Grabau et al, 2017). Although low densities were observed in our study, the population surprisingly increased sometimes after 3 months of black fallow in winter.…”
Section: Discussioncontrasting
confidence: 64%
“…It is known that black fallow in general has a negative effect on the population of P. penetrans (Pudasaini et al, 2006;Viaene et al, 2006). However, it was reported that at low population densities the number of nematodes can remain the same (Grabau et al, 2017). Although low densities were observed in our study, the population surprisingly increased sometimes after 3 months of black fallow in winter.…”
Section: Discussioncontrasting
confidence: 64%
“…Similarly, Tyler et al (1987) discussed that long-term tillage affected SCN population densities only 3 or 4 years after the establishment of their cropping system. Soil ecosystems may require attaining some degree of equilibrium before suppressiveness is noted, which implies that shifts in soil microbial communities due to cultural practices are incremental (Yeates et al, 1999;Venter et al, 2016;Grabau et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The use of Brassica and non-Brassica plants as biofumigation crops can be through maceration and incorporation of plant parts into the soil as green manure, through the use of seed meal, or as poor-host winter or summer cover crops (Hafez and Sundararaj, 2009;Rahman and Somers, 2005;Smith et al, 2004). Biofumigation is usually not as effective as chemical fumigation and biofumigant crops can also be good hosts to some of the target PPNs (Daryanto et al, 2018;Grabau et al, 2017;Monfort et al, 2007). The cost of biofumigation is still high and often not economically practical for farmers to apply (Clay et al, 2020;Dutta et al, 2019).…”
Section: Plant Volatile Compounds Against Plant-parasitic Nematodesmentioning
confidence: 99%